Experiences and perceptions of nutritional health and wellbeing amongst food insecure women in Europe: A qualitative meta-ethnography. (October 2022) - Bell, Zoë; Scott, Steph; Visram, Shelina; Rankin, Judith; Bambra, Clare; Heslehurst, Nicola
Abstract: Since the 2008 global financial crisis, there has been a rise in the number of people experiencing food insecurity. Particularly vulnerable are mothers with young children, pregnant women, and lone parents (the majority of whom are women). This systematic review and meta-ethnography of qualitative studies focused on women's experiences of food insecurity and how it affects their nutritional health and wellbeing. Six electronic databases (Medline, Scopus, Web of Science, EMBASE, CINAHL and ASSIA), were searched from January 1, 2008–July 10, 2021, and supplemented by searches of grey literature databases, relevant websites, examination of reference lists and citation searches. We adhered to PRISMA and eMERGe guidelines to improve the completeness and clarity of meta-ethnographic reporting. Methodological quality of the studies was assessed using the Critical Appraisal Skills Programme qualitative checklist. We identified 11, 589 unique records; we included 23 publications reporting data from 22 unique studies involving 647 women. Data were synthesised according to Noblit & Hare's seven phases of meta-ethnography. We identified two key themes - accessing sufficient food and embodying food insecurity - comprising seven sub-themes. Our meta-ethnography provides a progressive 'storyline' of women's experiences of food insecurity. This includes the ways in which women attempt to access sufficient food, are unable to meet their nutritional needs, and the ways in which this is embedded into their everyday lives and embodied in unhealthful physical, social, and mental nutritional health and wellbeing impacts. Our review emphasises that food insecurity directly and tangibly impacts women's nutritional health and wellbeing. It concludes that there needs to be greater recognition of the psychosocial impact of food insecurity on vulnerable women in addition to its impact on their nutritional health and wellbeing. Highlights: Women's experiences of food insecurity changed little, despite structural changes. There is a need for greater recognition of psychosocial impacts of food insecurity. Informal support networks helped mitigate the impact of food insecurity. Further qualitative research is needed amongst food insecure pregnant women. To mitigate food insecurity, policy must address the social determinants of health.